Procedures in the care of hand burns in the acute phase - Andrea Fernandes de Oliveira; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: The hand represents 3% of total body surface, but its involvement in severe trauma, such as burns, can lead to serious functional sequelae. The present study describes procedures in the care of patients in the acute phase with burns involving the hands. METHODS: 122 patients with thermal burns involving one or both hands were included in the study between August 2011 and July 2014. On initial physical examination, the extent and depth of the lesions were determined; deep and circular burns, with signs and symptoms of inadequate perfusion, had escharotomies performed to avoid the loss of extremity. Burns of partial deep thickness or full thickness on the back of the hands received tangential excision within 5 days after the trauma; partial skin grafting was performed on all patients before the 15th day of the trauma. RESULTS: Men represented the majority of cases (58%). In relation to the burn agent, flammable liquids caused 46.7% of admissions. In 50.8% of the cases, the burns were of partial deep thickness or of total thickness and required an operative procedure. No graft loss was identified in the group. Escharotomies were performed in 12.3% of the patients. CONCLUSION: The burned hand needs proper local attention and care, along with early excision and skin grafting.